Impact of Talent Management on Organisational Performance in Global Capability Centres (GCC): Challenges and Opportunities in Managing IT Professionals - Das Menon, Sai Kesava (Digital Repository of Theses, 2025)
The present research aimed at studying the impact of talent management on the performance of GCCs in particular, focusing on IT professionals. The existing study explore these research questions: to identify and assess factors that impact talent management on organisational performance in Global Capability Centres (GCCs) among information technology (IT) professionals; to explore talent management practices employed within Global Capability Centres (GCCs) that influence organisational performance; to explore and analyse the challenges and opportunities with managing IT talent in GCCs and to provide recommendations for developing talent management practices within GCCs. Sample size of the existing study include 600 IT professionals. The sample chosen from cities, namely, Bangalore, Pune and Hyderabad. Moreover, purposive sampling technique used for the existing study. Responses obtained from Information Technology (IT) Professionals on structured questionnaire. Various statistical techniques used to apply SPSS software version 26 to obtain conclusive results. The findings of study stated that engagement in decision-making and access to mentorship programs are the most important ways used for the identification of talent in GCCs. The factors of talent management relating to organisational performance within Global Capability Centres (GCCs) specifically for IT professionals are then analysed. The outcome of the research findings indicated that training and professional development programs along with the performance appraisal system is seen as the most prominent determinant that affects talent management and eventually its relationship with organisational performance among IT professionals in Global Capability Centres (GCCs). Second, it analysed the problems faced in managing IT talent in GCCs and found that changing skill requirements, mental health issues at work and burnouts, and competing for and attracting the best talent have been found to be the problems in managing IT talent in GCCs. In addition, the research analysed opportunities with managing IT talent in GCCs and mentioned that there is a possibility of leveraging a comprehensive pool of talent worldwide and emerging technologies for upskilling as an opportunity with managing IT talent in GCCs. Lastly, recommendations for developing talent management practices within GCCs analysed and stated that resources should be dedicated to ongoing education, discrete routes for career advancement should be created, and leadership programs should be made to stand out.